Promoting sport and the birth of Fiorentina: the contribution of Mayor Antonio Garbasso - Luti, Filippo (Il Colle di Galileo, 2024)
Antonio Garbasso was mayor and podestà of Florence from 1920 to 1928. During his mandate, in keeping with the strategies dictated by the fascist government in matters of sport, he promoted the construction of new facilities and worked to create a football association that could best represent Florence in the most popular sport. The article highlights the contribution that he, as mayor, made to the genesis of Fiorentina, a club founded in 1926 at the behest of the regime.